Hubungan Fungsi Kognitif Dengan Keseimbangan Pada Lansia Dengan Mild Cognitive Impairment - Muthiah Munawwarah; Atika Rezky Ramadhani; Jerry Maratis; Kesit Ivanali (LPPM Universitas Abdurrab, 2021)
Objective: To determine the relationship between cognitive function and balance in the elderly within Mild Cognitive Impairment (MCI) conditions at Posyandu, Talawi, Taratak Capo Hamlet. Method: This type of research is a descriptive correlative study using a cross sectional approach with the identification of purposive sampling on 72 sample. To assess cognitive levels, its make use of the Indonesian-Montreal Cognitive Assessment (INA-MoCA) questionnaire and balance measurement using the Time Up and Go Test (TUGT). Results: Correlation test with Pearson Product Moment obtained a significant relationship with p = 0.014 where p <value Î± (0.05) with r = 0.290, Which means there is a significant correlation between cognitive function and balance, where the higher the value of cognitive function, the higher balance value. Mean and standard deviation of Cognitive Function is 19.49 Â± 2.089 and 18.06 Â± 2.443 for balance. Conclusion: There is a relationship between cognitive function and balance in the elderly with Mild Cognitive Impairment (MCI) conditions in Posyandu, Talawi District, Taratak Capo Hamlet.